Family-based association tests: FBAT testing strategies for large-scale association studies - Lange, Christoph (Henry Stewart Talks, 2007)
Genome-wide association studies, Using the same data set for screening and testing, The conditional mean model, The FBAT-statistic, Genetic model under the alternative hypothesis, The concept of the conditional mean model, The screening technique for multiple markers, PBAT's screening techniques for multiple SNPs, The 3 steps of the screening technique, The Framingham heart study, Replication (recessive model) from other studies, Important observations from Herbert et al. (2006), Summary of the approach, Extensions, Software implementation